The History of the Insurance Market in Spain - Alemany, Ramon; Guillén, Montserrat (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2013)
We review the evolution of the insurance market in Spain up to the end of the 20th century. From a detailed account of the earliest written records of insurance dating from 1435 in Barcelona, we trace the strong influence that the markets in other West European countries have had on the Spanish market. We report how national insurance regulators have taken steps to promote greater liberalization and harmonization, while the creation of the European Union has led to the consolidation of the presence of many multinational insurers in the Spanish market. Today’s industry is mature, but the market penetration of insurance in Spain, and in the many countries in which Spanish insurers have expanded their business, still lags behind that of the leading economies.